Improvement of Tool Life in cold Forging by Locally Optimized Surfaces - Wagner, Kay; Putz, Alexander; Engel, Ulf (Journal of Materials Processing Technology, 2006)
Cold forging tools are exposed to extremely high loads. Depending on the most critical combination of the dominant factors characterizing the load which can be different even within the same tool, different damaging mechanisms will be initiated at least one of which is finally limiting tool life by either wear or fatigue. Since these failure mechanisms are mostly initiated on the tool surface the adjustment of surface properties to the local effective load combination might improve tool performance and increase tool life. In this paper, three different methods are being investigated: hard roller burnishing, laser beam treating and surface texturing. The determination of the tool load is a precondition for the selection of the appropriate surface treatment method. Thus, to find out which of the three methods can be used for tool surfaces in selected case studies, process simulation by finite-element-analysis becomes mandatory. Accordingly, FEA is used to select the optimum surface treatment which is then applied and tested in industrial applications. © 2006 Elsevier B.V. All rights reserved.
LFT Import::2019-07-16 (1261)
Keywords: Cold forging; Finite-element-analysis; Hard roller burnishing; Laser beam treating; Surface texturing; Surface treatment; Tool life